CRIMINOLOGY APPROACH IN SOLVING CYBER CRIME - Azhar AR; Yasmirah Mandasari Saragih; Fauzan (SEAN Institute, 2024)
Cybercrime, as a modern form of criminal activity, presents unique challenges due to its reliance on information and communication technology, the anonymity of perpetrators, and its cross-jurisdictional nature. This phenomenon encompasses a wide range of illegal activities, including hacking, identity theft, the spread of malware, on line fraud, and child exploitation in cyberspace. While legal frameworks and technological measures are essential in combating cybercrime, they are often insufficient to address the complex and evolving nature of cybercrime. The criminological approach provides a multidimensional perspective for understanding society's motives, behavior and responses to cybercrime. By integrating criminological theories, such as labeling theory and routine activity theory, this approach explores the root causes of cybercriminal behavior. Additionally, criminology offers insights into preventative measures and the development of more effective policies to mitigate cybercrime. This paper highlights the importance of applying a criminological framework to analyze cybercrime and proposes strategies for solving it through a combination of legal, technological interventions